DORĘCZENIA PISM PROCESOWYCH (UWAGI NA MARGINESIE CTH. 2,4,1 [A. 318/319] = C. 5,4,20) - Wiewiorowski, Jacek (Zeszyty Prawnicze, 2016)
THE NATURAL SCIENCES IN THE SERVICE OF PLEADINGS IN CASES INVOLVING MINORS: REMARKS ON CTH 2.4.1 [A. 318/319] = C. 5.4.20) Summary The subject of this article is the status of juvenile persons in Roman law, as exemplified by one of the constitutions of Constantine the Great, CTh 2.4.1 [a. 318/319] = C. 5.40.2, fragments of which are preserved in Theodosius’ Code of 438, and in an abridged version in Justinian’s Code of 534. In the first part of the article the author analyses the extremely controversial issue of the identity of the constitution’s addressee. In the second part he discusses the content of this constitution and the premises for its issue in the light of the Constantinian legislation on family matters and the way it was later interpreted. The article’s third part is an attempt to apply the natural and social sciences to the question of minors and their personality, and the examination of this issue as regards CTh 2.4.1 [a. 318/319] = C. 5.40.2. The author takes into consideration the basic data on the status of minors in Roman law, in the subsequent history of European law, and in non-European cultures. He concludes by making a series of observations on the potential for the application of the natural sciences in the study of Roman law, which could serve to confirm the timeless and universal nature of some of the solutions it prescribed.